The Role of Health security in Healthcare Settings: A Comprehensive Review - Manal Suhail Al-Otaibi, Sarah Asiri, Reem Musaad Al-Mutairi, Abdullah Fahd Al-Shammari, Sami Rabie Al-Dhafiri, Abdullah Mithyan Al-Muthabt, Tahani Al-Mutairi, Abdullah Mohammed Al-Hazmi, Mohammed Ayed AlDosari, Muhammad Mahmas Abdullah Al-Dossary; Saleh Ayed Sabar AlAnazi, Mushaira Mohammed MaHboub, Mohammed Mufdi Safouk Al-Shujai, Rahaf Hussein Al-Harbi, Salman Hassan Al-Shahrani, Saeed Ibrahim Saeed Al-Wazrah, Khaled Musa Al-Banaqi; Mufleh Mubarak Mohammed Al-Dosari, Shadi Hassan Khader Al-Harbi, Salman Ali Salman Al-Harbi, Abdullah Jahz Hadhar Al-Harbi (Journal of International Crisis and Risk Communication Research, 2024)
The increasing complexity of healthcare environments has necessitated a reevaluation of the role of health security within these settings. This comprehensive review explores the multifaceted responsibilities of security personnel in healthcare facilities, emphasizing their critical contributions to patient safety, staff support, and the overall security of the environment. As healthcare systems face rising patient volumes, heightened instances of violence, and the need for enhanced safety protocols, health security have evolved from traditional surveillance roles to proactive participants in fostering a culture of safety and security.Health security are often the first line of defense against potential threats, tasked with deterring violence, managing conflicts, and responding to emergencies. Their training encompasses crisis intervention techniques, effective communication, and an understanding of healthcare protocols, enabling them to navigate the unique challenges of healthcare settings. By maintaining a visible presence, security personnel not only deter aggressive behavior but also create a calming atmosphere for patients and staff, thereby enhancing the overall patient experience.Moreover, health security play a vital role in supporting healthcare staff, allowing them to focus on patient care without the added burden of safety concerns. Their involvement in emergency preparedness, conflict resolution, and compliance with safety regulations contributes to a safer working environment. Additionally, security personnel often serve as a bridge between patients and healthcare providers, facilitating communication and addressing concerns that may arise.This review highlights the importance of integrating security personnel into the healthcare team, recognizing their contributions to creating a safe and supportive environment. As healthcare organizations continue to adapt to evolving challenges, the role of health security will remain essential in ensuring the safety and well-being of patients, staff, and visitors. Ultimately, a collaborative approach that values the expertise of security personnel will lead to improved outcomes and a more effective healthcare system.